2016
DOI: 10.1590/1806-9282.62.03.212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of information retention and adherence to treatment in patients with gestational diabetes mellitus after multidisciplinary group

Abstract: Objective:To evaluate the retention of information after participation in multidisciplinary group in patients with gestational diabetes mellitus (GDM) through a phone contact. Method: 122 pregnant women diagnosed with gestational diabetes were included. After diagnosis of gestational diabetes, the patients were referred to the multidisciplinary group where they received medical, nutrition and nursing guidelines related to the disease. After three days these patients received one telephone call from a nurse, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…22 According to Sousa AM da S et al, 17% of GDM patients reported that the lancet of the needle and the duration of time it took to perform the SMBG test were obstacles to SMBG. 23 This is line with findings from other studies which mentions that patients find SMBG inconvenient because of pain, a cumbersome procedure, difficult to adopt SMBG as a daily routine practise, cost of the test strips and needles and carrying glucometer while travelling. 28,29 24 In 40 low-and lower-middle-income nations in Africa, South Asia, and Latin America, including India, a cross-sectional survey was carried out.…”
Section: Discussionsupporting
confidence: 89%
“…22 According to Sousa AM da S et al, 17% of GDM patients reported that the lancet of the needle and the duration of time it took to perform the SMBG test were obstacles to SMBG. 23 This is line with findings from other studies which mentions that patients find SMBG inconvenient because of pain, a cumbersome procedure, difficult to adopt SMBG as a daily routine practise, cost of the test strips and needles and carrying glucometer while travelling. 28,29 24 In 40 low-and lower-middle-income nations in Africa, South Asia, and Latin America, including India, a cross-sectional survey was carried out.…”
Section: Discussionsupporting
confidence: 89%
“…In other words, greater self-efficacy results in better patient management. In addition, among all kinds of patient education and lifestyle interventions, dietary changes are the most difficult recommendations to follow [ 14 ]. Factors that impede the implementation of medical recommendations include social activities such as eating out, cultural factors such as the consumption of specific kinds of food, family impacts such as the rejection of the concept of an individual serving size, obsolescent views on pregnancy, and women’s family-centered values and role commitments [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors may lead to consequences, such as reducing GDM management efficiency and causing poor pregnancy outcomes [ 13 ]. It was reported that good adherence of patients with GDM to clinical recommendations was observed, especially in relation to BG monitoring, but nutritional guidelines were less likely to be followed [ 14 ]. Given the limited intervention time window, the importance of continuous patient education and self-management supervision during the periods between antenatal care visits should be strongly emphasized.…”
Section: Introductionmentioning
confidence: 99%